Effective stiffness and thermal expansion of three-phase multifunctional polymer electrolyte coated carbon fibre composite materials. (31st March 2021) - Schutzeichel, M O H; Kletschkowski, T; Monner, H P
Abstract: Multifunctional composites including polymer electrolyte coated carbon fibres and polymer matrix systems gained recent interest in light-weight design related research areas. Compared to classical fibre reinforced plastics, the interphase, made by electropolymerisation on the fibre surface, represents a new, third material phase. The coating serves as ion-conducting separator in structural batteries and as insulating layer in energy transmitting multifunctional composites. The importance of this study is related to the fact, that multifunctional applications, based on such composites, are exposed to temperature changes in many cases. The coating material, acting as thin interphase, shows a significant temperature dependant Young's modulus, determining the overall macroscopic behaviour under thermal loads. The new influences on the effective elastic properties of the composite are determined in this work in a 3D microstructural simulation approach based on a unit cell geometry. For the first time, the resulting effective properties are discussed towards the state of research and future work. First, the effective elastic stiffness is computed by isothermal virtual material testing, applying unit strain modes on the unit cell. Second, a uniform temperature change is applied and the effective thermal expansion coefficients are computed. The results show that a change of stiffness in the coating domain has a great influence on the effective stiffness in the transversal isotropic plane. The effective thermal expansion of the composite is also highly sensitive to the thermal expansion behaviour of the coating phase. Main conclusions are drawn towards multiphysical material simulation: Influences of the coating material properties have to be taken into account to compute effective properties. In particular, it is necessary to include the temperature dependant stiffness and the coefficients of thermal expansion of the interphase, which affect effective properties significantly. A thermo-mechanic coupled microscale model is needed to represent in-situ properties of such composites for applications with heat exposure.